Expert System for Diagnosing Diseases in Rubber Plants using the Forward Chaining and Dampster Shafer Methods - Ningrum, Indri Ayu; Samsudin, Samsudin; Kusdiana, Alchemi Putri Juliantika (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Rubber plants are important crops in various countries. Rubber plants have many benefits for human life. Rubber plant diseases cause many losses to farmers. Lack of knowledge and information regarding the treatment of existing diseases is a factor that causes the decline in rubber latex productivity. Appropriate control is needed to overcome this problem. An expert system is one solution that can help farmers find out information about facts about rubber plant diseases. Expert systems are artificial intelligence sciences that can help provide solutions to problems faced by farmers as if they were consulting with experts. Therefore, a system was developed that can diagnose diseases in rubber plants using this method Forward Chaining and Dempster Shafer. Forward Chaining serves as a tool to draw conclusions from the information that has been established and Dempster Shafer to handle uncertainty in symptoms, so as to produce final conclusions. From 15 trial data, accuracy results were obtained at 93.33%. Thus method Forward Chaining and Dempster Shafer can be used to diagnose types of diseases in rubber plants because it has very good accuracy.